2012
DOI: 10.1002/j.2161-0045.2012.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Children's Career Aspirations: Relationship to Adult Occupations and Gender

Abstract: The authors explored the relationship between the career aspirations of 89 preadolescents from low socioeconomic backgrounds and the actual occupations of the working adults in their homes with regard to status, job gender identification, and interest (Holland, 1997). There was a significant relationship between boys’ career aspirations and the occupations of the working male adults in their homes, specifically job gender identification and interest. More adult males had stereotypically male jobs—classified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
3
32
0
2
Order By: Relevance
“…As researchers involved in supporting the school from an educational psychological perspective, we observed that children's career stories and hopes were not addressed in the school, home or community context. Moreover, the body of international and local research on career development in education reveals that there is a stronger focus on high school learners (Auger, Blackhurst & Wahl 2005;Flouri & Panourgia 2012;Schuette, Ponton & Charlton 2012), with limited emphasis at the primary school level Arulmani 2011b). In the context of unique pre-and post-democracy challenges, less than 4% of career research reports focus on the career development of children in South Africa, and most of these focus on white, middle-class high school learners (Arulmani, Van Laar & Easton 2001;Venter, Watson & Fouche 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As researchers involved in supporting the school from an educational psychological perspective, we observed that children's career stories and hopes were not addressed in the school, home or community context. Moreover, the body of international and local research on career development in education reveals that there is a stronger focus on high school learners (Auger, Blackhurst & Wahl 2005;Flouri & Panourgia 2012;Schuette, Ponton & Charlton 2012), with limited emphasis at the primary school level Arulmani 2011b). In the context of unique pre-and post-democracy challenges, less than 4% of career research reports focus on the career development of children in South Africa, and most of these focus on white, middle-class high school learners (Arulmani, Van Laar & Easton 2001;Venter, Watson & Fouche 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pembentukan sikap remaja tentang aspirasi karier merupakan hasil interaksi dengan keluarga (Febriani, Yusuf, & Iswari, 2016). Pembentukan aspirasi karier dimulai melalui pengenalan berbagai kemungkinan pilihan karier dalam keluarga (Schuette, Ponton, & Charlton, 2012).…”
Section: Pendahuluanunclassified
“…In 2010, women earned the majority of postsecondary degrees at all levels (62% of associates degrees, 58% of bachelor's degrees, 60% of master's degrees, and 52% of doctoral degrees) (NCES, 2012). In recent studies of elementary and middle school students, girls exhibited a preference for careers that were less sex-typed than boys, implying that girls are expanding their career aspirations and suggesting that this might lead to a less segregated professional workforce in the future (Blackhurst & Auger, 2008;Schuette et al, 2012).…”
Section: Gender Stereotypesmentioning
confidence: 99%
“…Parental expectations are especially predictive of the types of careers that females pursue (Jacobs et al, 2006), while working male adults in a child's household can impact boys' aspirations, more often than not stereotyping toward male-dominated careers (Schuette et al, 2012).…”
Section: Gender Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation